(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the advent of prominent social networking sites and blogs, citizens have taken upon themselves to undo the wrongs in the society. The SNS have given a voice to the citizens to advocate an opinion and advance the movement- Anna Hazare Movement, the Arab Uprising are all products of SNS influence. Like Print Journalism is attributed to have played a significant role in the freedom of independence, SNS can be rightly herald as the new age medium to mobilize support for the cause and fight for their right. Social media strengths lie in its interactive nature and the capability to reach millions of users within short span of time. Everybody has an opinion on SNS, it is probably one of the medium where there is no gatekeeper filtering news on the basis of race, religion, sex or ethnicity and if you have views voice it. Moreover, SNS is a versatile medium where you can couple powerful words with videos and pictures. Earlier the Government used to be dependent on opinion polls to gauge the mood of the public. With the introduction of social media the dependence on media has diminished as now SNS are the best indicator of the public atmosphere. It is not only ideal but a necessity for politicians to be present on SNS. Barrack Obama, the first African President of United States of America acknowledges the contribution of Social media for his win. In India, Narendra Modi, Prime Minister of India is called the first Facebook Prime Minister.